Guzmania sanluisensis (Bromeliaceae; Tillandsioideae), a new species from the fragmented montane cloud forests of northern Peru - Rojas-Fernandez, Marisela Analu; Gouda, Eric J.; Marcelo-Peña, José Luis (Phytotaxa, 2025)
Guzmania sanluisensis (Bromeliaceae) is described and illustrated, a new species from the severely fragmented cloud forests of the Jaén area, northern Peru. This species is recognized by its reddish to bright brown bracts and revolute white petals with purple spots at the apex. Its morphology is contrasted with related species. Additionally, information on ecological aspects, distribution, and conservation status is included.